An evolutive bounding surface plasticity model for early-age cemented tailings backfill under cyclic loading. Issue 117 (February 2019) - Lu, Gongda; Fall, Mamadou; Yang, Zhaohuan
Abstract: Cemented tailings backfill (CTB), an evolutive man-made soil or porous medium, is extensively utilized in underground mines as a sustainable solution for the disposal of tailings (mine waste) and/or ground control. At the early stages of curing, CTB is commonly saturated and weakly cemented, and thus subjected to the risk of seismically-induced liquefaction caused by mine blasts, rock bursts and earthquakes. The resulting intrusion of liquefied backfill mass into the mine tunnels may give rise to significant casualties and loss of production. In the present study, an evolutive bounding surface plasticity model is developed to capture the hydro-mechanical response of hydrating CTB under cyclic loading. Specifically, the changes of model components (yield and plastic potential functions, etc.) due to evolution of material properties are incorporated into the prototype bounding surface model. Then, the material property changes induced by binder hydration are determined and coupled to a binder hydration model that quantifies the curing process of CTB. Therefore, the developed model can be employed to assess the cyclic response of hydrating CTB at any given time of interest during its early age of curing when seismically induced liquefaction is of primary concern. The simulated results show good agreement with the experimental data for both monotonic and cyclic loadings. The proposed model can therefore provide more insight into the behavior of early-age CTB under seismic loading, and contribute to designing cost-effective CTB structures and assessing the risk of liquefaction. Highlights: Cemented tailings backfill (CTB) is an evolutive man-made soil. An evolutive bounding surface plasticity model for CTB under cyclic loading is developed. The model has been successfully validated against experimental data. The model provides more insight into the behavior of early-age CTB under seismic loading.